Dielectric Behaviour of Lead Nitrate with its Phase Transition - YADAVA, S.; PANDEY, B.K.; DUBEY, S.P.; GUPTA, R.N. (Asian Journal of Chemistry, 2010)
The dielectric constant of lead nitrate is measured between the temperature range 35 to 110 ºC. In present measurement, it has been found that the compound has lower value of dielectric constant below 38 ºC while it rises upto the value of 1200 around 40 ºC, after which it decreases upto the value of 400 at about 75 ºC, with some intermediate fluctuations. After 75 ºC the dielectric constant increases with temperature almost linearly upto 110 ºC. When the behaviour of compound is studied in cooling cycle, then pronounced hysteresis is found with certain intermediate fluctuations. The results have been explained on the basis of crystal structure changes and the possibility of free internal rotation of nitrate groups with in the crystal lattice at elevated temperature.